A Review On Brief Insight Into Spontaneous Human Combustion - Patil, Tulsi; Soni, Arun; Acharya, Sanjeev (Asian Journal of Pharmaceutical Research and Development, 2021)
The pseudoscientific principle of spontaneous human combustion (SHC) is the combustion of a living human body without an obvious external cause of ignition. Spontaneous Human Combustion eludes condition in which human body is found with huge segments of center parts of body reduced to fiery debris and substantially less harm to the head and extremities, and insignificant harm to the immediate surroundings of the body. The review was aimed to find the possible causalities of Spontaneous Human Combustion. There are basically two types of SHC and the etiology are found on the basis of some hypothesis. All the possible causative factors are covered and a treatment approach is also provided.